2017
DOI: 10.32601/ejal.460969
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Turkish-English Bilinguals’ Processing of Emotion Words in Their Two Languages

Abstract: There is a great deal of evidence showing that, in monolinguals, various emotional stimuli are processed by the brain in different ways. This view has found considerable support from studies conducted with verbal stimuli. In bilinguals, on the other hand, emotional processing is more complex, and is thought to be influenced mainly by two factors; age of language acquisition and proficiency. In this study, participants were forty-eight simultaneous / early bilinguals, who acquired both languages from birth, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Nişancı (2017) illustrated the role of extensive reading in promoting high school EFL learners’ implicit phonological knowledge and improving their word recognition fluency at large. Adopting a bilingual approach, Mergen and Kuruoğlu (2018) compared the lexical processing of Turkish-English bilinguals in both languages. The results coming from the lexical decision task that included letter strings of real and non-words revealed that Turkish-English bilinguals, who learned both languages from birth, responded faster and more accurately to real words than non-words both in Turkish and English.…”
Section: Classroom Processes and Instructional Practicesmentioning
confidence: 99%
“…Nişancı (2017) illustrated the role of extensive reading in promoting high school EFL learners’ implicit phonological knowledge and improving their word recognition fluency at large. Adopting a bilingual approach, Mergen and Kuruoğlu (2018) compared the lexical processing of Turkish-English bilinguals in both languages. The results coming from the lexical decision task that included letter strings of real and non-words revealed that Turkish-English bilinguals, who learned both languages from birth, responded faster and more accurately to real words than non-words both in Turkish and English.…”
Section: Classroom Processes and Instructional Practicesmentioning
confidence: 99%
“…For example, Sianipar, Middelburg and Dijkstra's (2015) longitudinal study with German-Dutch bilinguals found results supporting the privileged status of positive words in the participants' second language. Mergen and Kuruoglu (2017), employed a lexical decision task in a visual hemi-field paradigm, and reported that simultaneous bilinguals processed positive words faster than negative and neutral words in both languages. In another lexical decision task study, Ferre, Anglada-Tort and Guash (2018) reported faster response times for positive, but not for negative words for highly proficient bilinguals.…”
Section: Emotion Word Processingmentioning
confidence: 99%
“…The stimuli were taken from a previous study on emotion word processing in simultaneous bilinguals (Mergen & Kuruoglu 2017). We used two sets of words.…”
Section: Stimulimentioning
confidence: 99%
“…However, to the best of the authors' knowledge, there are very few studies that investigated Turkish language from a psycholinguistic perspective, which is spoken as a native language and being learned as a foreign / second language by millions of people today. The existing literature generally focuses on language pathology (Sadiyeva, 2004;Maviş & Özbabalık, 2006;Toğram, Çıkan & Duru, 2013;Ulusoy & Kuruoğlu, 2013), language learning and acquisition (Haznedar, 2007;Dolgunsöz & Sarıçoban, 2016;Tok & Yıgın, 2013;Sarıca, 2014;Özge, Marinis & Zeyrek, 2015) and bilingualism (Belet, 2009;Çeltek, 2014;Mergen & Kuruoğlu, 2016;2017). This study aimed to fi ll this gap in the literature by investigating lexical processing in Turkish, how emotional workload affect lexical processing of Turkish words and their hemispheric organization.…”
Section: Introductionmentioning
confidence: 99%